Mandibular‐pelvic‐patellar syndrome is a novel PITX1‐related disorder due to alteration of PITX1 transactivation ability. Issue 9 (15th July 2020) - Morel, Godelieve; Duhamel, Céline; Boussion, Simon; Frénois, Frédéric; Lesca, Gaetan; Chatron, Nicolas; Labalme, Audrey; Sanlaville, Damien; Edery, Patrick; Thevenon, Julien; Faivre, Laurence; Fassier, Alice; et al.
Abstract: PITX1 is a homeobox transcription factor essential for hindlimb morphogenesis. Two PITX1 ‐related human disorders have been reported to date: PITX1 ectopic expression causes Liebenberg syndrome, characterized by malformation of upper limbs showing a "lower limb" appearance; PITX1 deletions or missense variation cause a syndromic picture including clubfoot, tibial hemimelia, and preaxial polydactyly. We report two novel PITX1 missense variants, altering PITX1 transactivation ability, in three individuals from two unrelated families showing a distinct recognizable autosomal dominant syndrome, including first branchial arch, pelvic, patellar, and male genital abnormalities. This syndrome shows striking similarities with the Pitx1 −/− mouse model. A partial phenotypic overlap is also observed with Ischiocoxopodopatellar syndrome caused by TBX4 haploinsufficiency, and with the phenotypic spectrum caused by SOX9 anomalies, both genes being PITX1 downstream targets. Our study findings expand the spectrum of PITX1 ‐related disorders and suggest a common pattern of developmental abnormalities in disorders of the PITX1–TBX4–SOX9 signaling pathway.